Osteoarticular Infections in Pediatric Hospitals in Europe: A Prospective Cohort Study From the EUCLIDS Consortium - Trobisch, Andreas; Schweintzger, Nina A.; Kohlfürst, Daniela S.; Sagmeister, Manfred G.; Sperl, Matthias; Grisold, Andrea J.; Feierl, Gebhard; Herberg, Jethro A.; Carrol, Enitan D.; Paulus, Stephane C.; Emonts, Marieke; van der Flier, Michiel; et al. (Frontiers in Pediatrics, 2022)
Background: Pediatric osteoarticular infections (POAIs) are serious diseases requiring early diagnosis and treatment. Methods: In this prospective multicenter cohort study children with POAIs were selected from the European Childhood Life-threatening Infectious Diseases Study (EUCLIDS) database to analyze their demographic, clinical and microbiological data. Results: A cohort of 380 patients with POAIs, 203 with osteomyelitis (OM), 158 with septic arthritis (SA) and 19 with OM + SA, was analyzed. 35 were admitted to the Pediatric Intensive Care Unit, six suffered from shock, one needed an amputation of the right foot and of four left toes, and two had skin transplantation. According to the Pediatric Overall Performance Score, 36 (10.5%) showed a mild overall disability, 3 (0.8%) a moderate and 1 (0.2%) a severe overall disability at discharge. A causative organism was detected in 65% (247/380) of patients. Staphylococcus aureus (S. aureus) was identified in 57.1% (141/247) of microbiological confirmed cases, including 1 (0.7%) Methicillin-resistant Staphylococcus aureus and 6 (4.2%) Panton-Valentine leukocidin producing (PVL) S. aureus, followed by Group A Streptococcus (18.2%) and Kingella kingae (8.9%). Kingella kingae and PVL-production in S. aureus were less frequently reported than expected from the literature. Conclusion: POAI’s are associated with a substantial morbidity in European children, with S. aureus being the major detected pathogen. In one third of patients no causative organism could be identified. Our observations show an urgent need for the development of a vaccine against S. aureus and for the development of new microbiologic diagnostic guidelines for POAI’s in European pediatric hospitals.